Nutritional status of healthy and declining citrus (Citrus reticulata) orchards - DEY, J K; SINGHA, D D (The Indian Journal of Agricultural Sciences, 2013)
Healthy and declining citrus (Citrus reticulata Blanco) orchards of hill s region of Assam were surveyed for ascertaining nutritional factor causing citrus decline. Both healthy and declining orchards of Karbi Anglong were high in 1, but low in both Ca and P in respect of foliar content. In Karbi Anglong, fruit yield positively correlated with foliar K content. Effect of foliar concentration of K on the fruit yield was however, indirect. In North Cachar Hills, orchards were mostly low in Ca but commonly high in K in respect of foliar content. Declining orchards of North Cachar Hills were low in foliar P content.In North Cachar Hills, low/fruit yield was associated with lower concentration of available Ca in soils, lower foliar Ca content, and narrow Ca : Mg ratio in leaf. Foliar concentration of K was regulated by soil concentration ratio of K : Ca + Mg or K : Mg in North Cachar Hills, and N : Ca in Karbi Anglong, whereas foliar Ca concentration was regulated by soil concentration ratio of K : Mg in both the locations. Soil-available Ca content, more than 288 kg/ha, and foliar Ca : Mg ratio, more than 8.70 were associated with healthy crop in North Cachar Hills. Soil parameters to the depth of 45 cm rather than surface layer (0-15 cm) were significanttly correlated with fruit yield and foliar nutrient content.